2021
DOI: 10.20471/acc.2021.60.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Breastfeeding Educational Intervention on Secondary School Students after 6 Months

Abstract: SUMMARY Breastfeeding attitudes are already being formed in the years of preadolescence-adolescence, which means that the educational program should be focused on this age group. For this purpose, many authors suggest that school should be used as an established educational institution and therefore they are developing different education programs. The authors offered an educational program adapted to the cultural, sociological, legal, health, and other specificities of the community to which the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
1
0
2
Order By: Relevance
“…Moreover, physical and social problems are not only identi ed early but also managed in time before breastfeeding. (30,31) Providing education during adolescence may provide support to breastfeeding mothers. The WHO reported that every year, 21 million adolescents aged 15-19 years become pregnant in low-income countries, and approximately 12 million have had babies.…”
Section: 7% Respectively)mentioning
confidence: 99%
“…Moreover, physical and social problems are not only identi ed early but also managed in time before breastfeeding. (30,31) Providing education during adolescence may provide support to breastfeeding mothers. The WHO reported that every year, 21 million adolescents aged 15-19 years become pregnant in low-income countries, and approximately 12 million have had babies.…”
Section: 7% Respectively)mentioning
confidence: 99%
“…Više radova je analiziralo edukativne programe o dojenju koji se primjenjuju u srednjim školama (6,7), veleučilištima (8) i fakultetima (9) zdravstvenih smjerova u Hrvatskoj. Analizirana je i učinkovitost primijenjene edukacije (10)(11)(12). Rezultati istraživanja potvrđuju da pozitivan učinak imaju samo programi edukacija o dojenju koji se provode strukturirano, kontinuirano i koordinirano, što je sukladno ranijim radovima drugih autora (13).…”
Section: Uvodunclassified
“…Josipom Grgurićem podržali su ova istraživanja. Rezultati su potvrdili da ponuđeni program rezultira pozitivnim promjenama znanja, stavova i namjera učenika o dojenju u statistički značajnoj mjeri u trajanju najmanje šest mjeseci po završetku programa (14)(15)(16).…”
unclassified